1991
DOI: 10.1113/jphysiol.1991.sp018899
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of motor units in the wrist extensor muscles during the tonic vibration reflex in man.

Abstract: 1. Single motor unit activity was recorded in the extensor carpi radialis longus and extensor carpi radialis brevis muscles of five healthy human subjects, using metal microelectrodes. 2. Motor units were characterized on the basis of their twitch contraction times and their force recruitment thresholds during voluntary imposed-ramp contractions. 3. The discharge patterns of forty-three motor units were studied during tonic vibration reflex elicited by prolonged (150 s) trains of vibration (30 Hz) applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 39 publications
0
43
0
Order By: Relevance
“…However, TVR seems also to be modulated by alterations in spindle sensitivity through γ control (Matthews 1966;Ribot-Ciscar et al 2000). By applying a vibration directly to the tendon, previous studies have suggested TVR to be composed of motor unit activity synchronized and unsynchronized with the vibration cycle (Hori et al 1989;Romaiguère et al 1991). Studies have also indicated that TVR may contribute to muscle fatigue and/or increase the risk of cumulative trauma disorders observed after repetitive exposure of the hand to vibration (Park and Martin 1993).…”
Section: Introductionmentioning
confidence: 99%
“…However, TVR seems also to be modulated by alterations in spindle sensitivity through γ control (Matthews 1966;Ribot-Ciscar et al 2000). By applying a vibration directly to the tendon, previous studies have suggested TVR to be composed of motor unit activity synchronized and unsynchronized with the vibration cycle (Hori et al 1989;Romaiguère et al 1991). Studies have also indicated that TVR may contribute to muscle fatigue and/or increase the risk of cumulative trauma disorders observed after repetitive exposure of the hand to vibration (Park and Martin 1993).…”
Section: Introductionmentioning
confidence: 99%
“…TVR is derived from the stimulation of Ia-afferents when a sinusoidal vibration is directly applied to a muscle or a tendon [13], [15], [16] and composed of motor unit activity synchronized and unsynchronized with the vibration cycle [17], [18]. Through TVR, muscles try to achieve vibration dampening and joint stiffening by preferential recruitment of faster motor units [13], [19].…”
mentioning
confidence: 99%
“…These reflex contractions may be of two types, depending on the context in which the vibratory stimulation is applied. Vibration may evoke a tonic vibratory reflex (TVR) in the parent muscle when the subject looks at his or her arm, a response that can involve both mono-and polysynaptic spinal pathways, as well as supraspinal processes (13,14,19,28). When the subjects close their eyes, tendon vibration induces a sensation of illusory movement, which is accompanied, in 70% of healthy subjects, by a contraction of the muscle(s) antagonistic to the vibrated muscle [antagonist vibratory response (AVR)] (4,5,10,26).…”
mentioning
confidence: 99%